Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15792725 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1125 ZenodoArchiveConcept: 15792724
Keywords: _r:AddedByMyEducationEvidence

Leveraging Existing Technology in Low-Resource Settings to Support Learning: Conceiving and developing implementation plans for schools - Hayat, Amal; Flam, Rebekka; Handigol, Apoorva (EdTech Hub, 2025)
This document serves as a practical guide for implementers and decision-makers on how available technologies can effectively support teaching and learning in schools worldwide. Drawing on existing evidence of successful EdTech interventions in low-resource settings, particularly within Southeast Asia, it offers guidance on the essential steps in the early phases of EdTech implementation. The report also provides recommendations for transitioning from the initial conception phase to developing a comprehensive implementation plan. Keywords: EdTech implementation guide; low-resource settings; ASEAN; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14727493 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1088 ZenodoArchiveConcept: 14727492
Keywords: _r:AddedByMyEducationEvidence